2018
DOI: 10.4314/ahs.v18i2.24
|View full text |Cite
|
Sign up to set email alerts
|

Non- adherence to anti-retroviral medication in Shiraz, 2014: a cross sectional study

Abstract: BackgroundMedication adherence is a dynamic and complex behavioral process, which is strongly influenced by personal, social and environmental factors.ObjectivesTo determine the prevalence and factors affecting non-adherence to medication among HIV-infected patients.Methods and materialsDesignA cross-sectional study.SettingVoluntary Counseling and Testing Center (VCT), Shiraz, Fars province, in the South of Iran.PatientsAmong HIV-positive patients who received anti-retroviral therapy, 214 adult patients were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
(25 reference statements)
1
9
1
Order By: Relevance
“…However, cross-sectional study conducted in Shiraz showed that prevalence of nonadherence was 30.4%. 19 This small difference between our study and that of study conducted in Shiraz may be due to the fact that studies were done in different sociocultural areas. More over the difference could be due to differences in design of the studies that is in our study we used pre-post intervention study but the other study is cross sectional.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…However, cross-sectional study conducted in Shiraz showed that prevalence of nonadherence was 30.4%. 19 This small difference between our study and that of study conducted in Shiraz may be due to the fact that studies were done in different sociocultural areas. More over the difference could be due to differences in design of the studies that is in our study we used pre-post intervention study but the other study is cross sectional.…”
Section: Discussioncontrasting
confidence: 65%
“…3 Study in Brazil found that nonadherence to ART among patients initiating the therapy was 36.9% in 2005. 4 A study conducted in Northwest Ethiopia indicated that nonadherence to ART among adult hospitalized patients was 19.1% in 2014. 5 Nonadherence to ART is related to different factors.…”
Section: Introductionmentioning
confidence: 99%
“…The study is higher than studies done in Northern Ethiopia (62.3%), 24 Southern Ethiopia (60%,56%), 25,26 Eastern Ethiopia (65%), 27 Western Africa (62.6%), 28 Southern-central Africa (63.81%), 29 Southern Africa (70.8%), 30 and Western Asia (69.6%). 31 This variation might be due to differences in adherence measurement, and socio-demographic characteristics. In this study, relationships were found between ART adherence and different variables.…”
Section: Discussionmentioning
confidence: 99%
“…HIV of course is the big story here, with authors reporting adherence to ART23, physical activity24 and disputes over HIV diagnosis by ELISA25, hepatitis C26 and surveillance of epidemic prone diseases 27…”
Section: Infectionsmentioning
confidence: 99%